The Effectiveness of The Use Game Based Learning on Student's Motivation and Learning Outcomes in Camera Movement Engineering Materials - Marcella, Chellsy; Fauziyah, Syifa; NdaruLaksito, Jimad (Universitas Veteran Bangun Nusantara, 2022)
The shift of conventional learning media to more modern learning media is a must for the world of education to be able to adapt to the development of science and technology. This study was conducted to analyse the effectiveness of the use of game-based learning on motivation and student learning outcomes on the subject of camera movement techniques. Data collection uses tests to measure learning outcomes and checks to measure learning motivation. The data analysis technique uses normalized gain (N-Gain). The application of the game-based learning model also improves learning outcomes. The average value of the pre-test was 76.41 and increased at the post test of 90.28. Based on the KKM score, 37 people or 94.9% have completed learning. This shows that there is an increase in learning outcomes seen from the average value. The average value of normalized gain (N-Gain) is 0.60, so the game-based learning quizzes method is quite effective in improving learning outcomes. Teachers should reduce the lecture method by increasing the active play method.